PENGARUH PENERAPAN MODEL THINK TALK WRITE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 AMPEK ANGKEK - Hayatun Fadhilah (Jurnal Edukasi dan Penelitian Matematika, 2021)
The main foundation in learning mathematics is mastering concepts. However, in reality at SMP Negeri 1 Ampek Angkek, the ability to understand the concepts of class VIII students is still not optimal. Not optimal students in understanding this concept will affect other mathematical abilities. One of the efforts to improve students' understanding of mathematical concepts is thelearning model TTW. The type of research used is a quasi-experimental withstudents of class VIIISMP Negeri 1 Ampek Angkek in the academic year 2021/2022 as the research population. Kelas VIII.1 and VIII.2 as an experimental class as the control class. The instrument of this research is in the form of a concept understanding test in the form of an essay question with Cartesian coordinates material. The data from the concept understanding test were analyzed with the help ofsoftware minitab. The final test to draw the conclusion of this research is using t-test . Based on the results of the final test analysis, it was obtained that P-value = 0.002, meaning that the understanding of mathematical concepts of students who studied with thetype of learning model Think Talk Write was better than the understanding of mathematical concepts of students who studied with direct learning models in class VIII SMP N 1 Ampek Angkek . Thus, it can be concluded that there is an influence of the TTW learning model on the understanding of students' mathematical concepts.  Keywords -. Understanding mathematical concept, Cooperative learning model of Think Talk